Modification of Carbon Paste Electrode with Crown Ether (Dibenzo-18-Crown-6) for Ascorbic Acid Analysis Using Differential Pulse Voltammetry Method - Irdhawati Irdhawati; Manuntun Manurung; Anisha Maulinasari (ALCHEMY Jurnal Penelitian Kimia, 2015)
In this research, the modified carbon paste electrode with crown ether (dibenzo-18-crown-6) has been prepared, for determination of ascorbic acid. Some of parameters observed were optimization of crown ether composition in carbon paste, pH of solution, linear concentration range, limit of detection, reproducibility, and recovery. The optimum performance of the prepared electrode was applied for determination of commercialsampleswhich contain of ascorbic acid. The result of this research showsthat the optimum composition of crown ether in carbon paste is 0.6 % at pH 4. Linear range of concentration obtained is from 2 - 200 μM. The detection limit and percentage of recovery are 1.243 μM and 101.31 %, respectively. The modified electrode has HorRat value less than 2, it indicates a good reproducibility. Analysis of 4 commercial samples which contain of ascorbic acid were in agreement with the content listed in the label with the suitability of 94 - 100 %.